Geomorphic Analysis in Determining Tectonic Activity Affected by Sumatra Fault in Liwa Region and Its Surrounding Area, Lampung, Indonesia - Yudhicara, Yudhicara; Muslim, Dicky; Sudradjat, Adjat (Geological Agency, 2017)
DOI: 10.17014/ijog.4.3.193-208The study discusses about characteristics of Sumatra Fault and its tectonic activity in Liwa and the adjacent area. The research uses quantitative methods of verification hypothetical deduction, which starts from the general approach, then it pursues into more specialized and focused ones. While the research work includes field measurements, remote sensing with GIS, and geomorphologic analysis using morphometry, such as: sinousity of mountain front (Smf), percentage of facets, ratio of the width and height of the valley (Vf), bifurcation ratios of the river (Rb), drainage density (Dd), shape of the watershed basin area (Bs), hypsometric curves (HI), and gradient index of stream length (SL). Basically, two blocks separated by the Sumatra Fault do not have a significant difference in tectonic activity, but the tectonic activity change can be seen when the studied area is divided into three blocks (northwest, middle, and southeast), then the change in each part can clearly be seen. Apparently, the tectonic activity in the studied area starts from the southeast continues toward the northwest. It is proved by this research, that geomorphological parameters which are associated with mountain fronts and watershed systems demonstrate the value of the activity increases towards the northwest. Hypsometric curves and a river analysis show that the tectonic activity in the northwest is relatively in a young stage, while towards the southeast it is getting in a mature stage.